Non-traditional activities and bank efficiency: empirical evidence from the Chinese banking sector during the post-reform period - Sufian, Fadzlan; Habibullah, Muzafar Shah (Inderscience Publishers, 2009)
This paper examines the impact of non-traditional activities on the China banking sector’s technical and scale efficiency during the post-reform period 2000–2005. The paper follows the procedures set by Isik and Hassan (2003) by omitting the off-balance sheet items first, before adding it as an additional output variable in the analysis. The empirical findings suggest that the State Owned Commercial Banks’ technical efficiency are enhanced attributed to improvement in scale efficiency, the Joint Stock Commercial Banks have exhibited a higher levels of technical efficiency attributed to improvement in pure technical efficiency.